2000
DOI: 10.1107/s0907444999014948
|View full text |Cite
|
Sign up to set email alerts
|

Towards the charge-density study of proteins: a room-temperature scorpion-toxin structure at 0.96 Å resolution as a first test case

Abstract: The number of protein structures re®ned at a resolution higher than 1.0 A Ê is continuously increasing. Subatomic structures may deserve a more sophisticated model than the spherical atomic electron density. In very high resolution structural studies (d < 0.5 A Ê ) of small peptides, a multipolar atom model is used to describe the valence electron density. This allows a much more accurate determination of the anisotropic thermal displacement parameters and the estimate of atomic charges. This information is of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
64
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 36 publications
0
64
0
Order By: Relevance
“…Efforts have been made toward aspherical-atom re®nement using the limited model. The study on the scorpion Androctonus australis Hector toxin II (room-temperature data of 0.96 A Ê resolution) also revealed bonding effects, but led to an underestimation of the net charges on the peptide-bond atoms (Housset et al, 2000). In the case of the protein crambin (0.54 A Ê resolution, low-temperature data), the re®nement resulted in multipole parameters within 25% of those from the transferable database but lower bonding features than predicted by the database (Ferna  ndez-Serra et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have been made toward aspherical-atom re®nement using the limited model. The study on the scorpion Androctonus australis Hector toxin II (room-temperature data of 0.96 A Ê resolution) also revealed bonding effects, but led to an underestimation of the net charges on the peptide-bond atoms (Housset et al, 2000). In the case of the protein crambin (0.54 A Ê resolution, low-temperature data), the re®nement resulted in multipole parameters within 25% of those from the transferable database but lower bonding features than predicted by the database (Ferna  ndez-Serra et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Electron densities based on multipole models of proteins have previously been considered for crambin Schmidt et al, 2011), human aldose reductase (Guillot et al, 2008) and trypsin (Schmidt et al, 2003). Multipole parameters have been refined in these cases, whereas for scorpion toxin (Housset et al, 2000) a multipole model was developed with multipole parameters fixed to database values. A similar approach was used for a series of neuraminidase-inhibitor complexes (Dominiak et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, however, it has been demonstrated that charge density refinement for biological macromolecules can also be carried out if the diffraction resolution is high enough and if the atomic thermal motion is sufficiently low. For example, the application of charge density refinement to the structure of a scorpion protein at 0.96-Å resolution showed visible bonding density between some main-chain atoms (21). The best example of charge density analysis applied to biological macromolecules, however, is provided by exhaustive refinement, at the ultrahigh resolution of 0.54 Å, of the valence electron distribution in crambin, a small protein with 46 residues (22).…”
mentioning
confidence: 99%